Elements that influence customer satisfaction in buying a house: A study on Perbadanan Kemajuan Negeri Selangor (PKNS) Bangi / Farhan Zul Faqar Md Zain - Md Zain, Farhan Zul Faqar (Faculty of Business and Management, 2004)
The purpose of these studies is to ascertain and expose the elements that influence customer satisfaction at PKNS Bangi and also to suggest the possible solution that can be used to overcome certain problem regarding customer satisfaction. This study will require researcher to compete its practical training and experienced real working environments while doing or conducting its research studies under the supervisions of PKNS Bangi assistance manager which is Encik Mahfizul. The information that been handed by him to the researcher had been use to develop a related questionnaire which required during the studies. A questionnaire is used as the datagathering tool and proves to be the most effective method. In this study convenience sampling has been used. The sample size of 50 respondents and data collection period within one week at the newest populated housing at section 4 Bandar Baru Bangi. The result of these study we concluded using latest computer software SPSS. The conclusion of these study based on the research findings found that most of the respondent did not response positively when the question been distributed, most of them complaint that they did not have time to answered such question. Which than lead to incremental data collection period. There are several areas that PKNS Bangi needs and can be improve. First the service provided to the customer such as lawyer and bank. It is identify that most respondent complaint that the location of lawyer office are to far away from their current home and for the bank most of them did not understand completely about the loan regulation been applied. Second the product/goods itself, PKNS Bangi needs to ensure the materials used to build the house are good or excellent to ensure the house have longer life span. A few recommendations that researcher want to suggest is that to better improve the customer service section of PKNS Bangi such as counter service, telephone service and web services. This part of service is important because it mark how the PKNS Bangi handle its customer.